Hubungan Antara Kecerdasan Intrapersonal Dengan Prestasi Belajar pada Mata Pelajaran Pendidikan Kewarganegaraan - Rukmana Agung Koswara; Sumardi Sumardi (FKIP UNIVERSITAS PAKUAN, 2015)
The study is aimed at finding out a positive correlation between students’ intelligence and their achievement on civics. The research employed quantitative associative approach and correlation study. It was conducted in December 2014. The objects of the research were the students of class VA and VB of SD Negeri Ciomis 1 in the district of Ciomas, Bogor. There were totally 41 respondents. To validate the instrument for measuring interpersonal intelligence, Pearson Product Moment formula was used. To test the reliability of the instrument, Alpha Cronbach formula was employed. The data of students’ achievement were taken from their scores of the report. After being tested for its normality using liliefors, both of the sample groups are normally distributed since both of them have the score of L calculated of (0.1328) and Ltable of (0,1373) and when it was tested for homogeneity, the score was Fcalculated of (8,83) , Ftable (43,775). The hypothesis was tested by using the technique of simple regression analytical relation with Y= 66,51 + 0,13X which means that the correlation is significant. In the research, when there is one level increase of intrapersonal intelligence, then it will increase the students’ achievement on civics for 13 units. The simple correlation test shows that r = 0.89 which means that the correlation is very strong and the coefficient of determination is (r2) = 0.79 which means that the intrapersonal intelligence contributes as much as 79% on the students’ achievement on civics. Based on the research result, it can be concluded that there is a positive correlation between intrapersonal intelligence and students’ achievement on civics.